The Muhammadiyah’s 47th Congress and “Islam Berkemajuan” - Ali, Muhamad (Studia Islamika, 2015)
The Muhammadiyah’s 47th congress or muktamar in Makassar, South Sulawesi, 18-22 Syawwal 1436 H or 3-7 August 2015, had its theme “Enlightenment Movement toward A Progressive Indonesia”. In the opening ceremony, the chairman of the central board, Din Syamsuddin, took the occasion to propose that three of the Muhammadiyah’s leaders, namely Kahar Mudzakir, Ki Bagus Hadikusumo, and Kasman Singodimejo, be recognized as national heroes. President Ir. Joko Widodo has yet to respond to the proposal, but expressed his high appreciation for the Muhammadiyah’s contributions as the enlightenment and progressive movement to the Muslim community and the nation through its schools and universities, hospitals, and others. Joko Widodo pointed to the challenge of the nation’s plurality, and invited participants to continue to give their enlightening contributions to the nation and to the world.DOI: 10.15408/sdi.v22i2.1978